(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To examine the relationships among retinal structural changes, apoptosis marker, and retinal metabolic parameters in animals with experimental diabetes and high myopia. Material and Methods: Fifty-five Wistar rats (age, 2 weeks) were used in experiments. High myopia was produced in animals by surgically fusing the eyelids of both eyes. In some rats with myopia, diabetes was induced by streptozotocin injection (a subdiabetic dose of 15 mg/kg body weight, intraperitoneally for 5 days). Rats were assigned to four groups: group 1 (myopia alone), group 2 (diabetes alone), group 3 (both myopia and diabetes), and group 4 (healthy controls). In two months, histomorphological studies were conducted, and the number of retinal ganglion cells (RGCs) was determined in the field of view. The clinical status of the retina was assessed by ophthalmoscopy. Retinal fragmented DNA (fDNA) level was determined by spectrophotometry. Statistical analysis was used to examine the relationships between retinal structural and metabolic changes. Parametric (Student t-test) and non-parametric tests (Mann-Whitney U test, Kruskal-Wallis test and Spearman rank correlation analysis) were employed. Results: Morphometric studies demonstrated that the number of RGCs was substantially reduced in diabetic animals compared to controls, and increased in diabetic animals with myopia compared to animals with diabetes alone. Retinal fDNA level was increased in diabetic animals compared to controls, and reduced in diabetic animals with myopia compared to animals with diabetes alone. There was a negative correlation between the number of RGCs and retinal fDNA level for animals with diabetes alone and diabetic animals with myopia. A positive correlation was found between the number of RGCs and retinal metabolic parameters. Conclusion: Myopization can prevent the development of retinal diabetic complications. Retinal energy processes, brain-derived neurotrophic factor and low early apoptosis of RGCs are involved in the regulation of protection from diabetic retinopathy.